إشكالية مفهوم الخلافة الأموية - ضفار، عامر عبدالرزاق (جامعة العربي بن مهيدي - أم البواقي, 2022)
يهدف البحث إلى توضيح ماهية الحكم الأموي حسب الشرع الإسلامي، وتوضيح حكم التزام المسلمين بالطاعة والبيعة في حالة الملك الوراثي، وهل يصح إطلاق مصطلح الخلافة الأموية شرعا. فلم يكن حقيقة النزاع بين سيدنا علي بن أبي طالب وسيدنا معاوية بن أبي سفيان رضي الله عنهما على منصب الخلافة، بل من أجل البت في قضية القصاص من قتلة عثمان بن عفان رضي الله عنه. ويصح أن يطلق على الحكم الأموي مصطلح "الخلافة" مجازا، ما دمت قد حققت مفهوم الخلافة التي اتفق عليها الجمهور. The research aims to explain the nature of the Umayyad rule according to Islamic law, and to clarify the rule of Muslims' obligation to obey and pledge allegiance in the case of the hereditary monarch, to clarify the rule of the Umayyad Caliphate according to Sharia. The reality of the dispute between our master Ali bin Abi Talib and our master Muawiyah bin Abi Sufyan, may God be pleased with them, is not over the position of caliphate, but for the purpose of deciding the issue of retribution for the killers of Othman bin Affan, may God be pleased with him. It is correct to call the Umayyad rule a metaphorical term "Caliphate", as long as it has achieved the concept of the Caliphate that was agreed upon by the public..
Keywords: الدولة الأموية -- ولاية العهد -- الخلافة الإسلامية -- حكم الخلافة شرعا -- الخلفاء الأمويون